2018
DOI: 10.1039/c8qo00964c
|View full text |Cite
|
Sign up to set email alerts
|

A facile approach to synthesize azaindoline functionalized spirocarbocyclic scaffolds via a Pd-catalyzed cascade cyclization/dearomatization process

Abstract: Azaindoline functionalized spirocarbocyclic scaffolds bearing two all-carbon quaternary centers are synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 54 publications
0
10
0
2
Order By: Relevance
“…In 2018, Yao and Lin reported that alkylpalladium(II) intermediates could be captured with an o ‐alkynylaniline via an anti ‐nucleopalladation process (Scheme 1 c), [6a] often referred to as the Cacchi reaction [16] . In concert with reports from Chen and Wu, [6b,c] along with the Yao lab [6d] employing phenol dearomatization and imines, respectively, we hypothesized that these reactions could all operate under the same conditions. A growing interest in coupling the Cacchi reaction with other Pd‐mediated processes has emerged [17] .…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…In 2018, Yao and Lin reported that alkylpalladium(II) intermediates could be captured with an o ‐alkynylaniline via an anti ‐nucleopalladation process (Scheme 1 c), [6a] often referred to as the Cacchi reaction [16] . In concert with reports from Chen and Wu, [6b,c] along with the Yao lab [6d] employing phenol dearomatization and imines, respectively, we hypothesized that these reactions could all operate under the same conditions. A growing interest in coupling the Cacchi reaction with other Pd‐mediated processes has emerged [17] .…”
Section: Methodsmentioning
confidence: 75%
“…Similar to lactone 3 f , harsher reaction conditions were required for the imine cyclization, however, 3 h was successfully produced in good yield and moderate ee . Attempted phenol dearomatization did not generate any cyclohexadienone products [6b,c] . Similarly, malonates and tosyl‐protected benzylic amines failed to furnish the desired products.…”
Section: Methodsmentioning
confidence: 96%
“…For instance, Luan, , Gulías, Lam, and You independently reported a series of transition-metal-catalyzed [3 + 2] spiroannulations of substituted phenols with various unsaturated compounds under oxidative reaction conditions, leading to the formation of various diversely functionalized spirocyclohexadienone molecules in good yields. Recently, we have reported a cascade Heck cyclization/phenol dearomatization process catalyzed by palladium from well-designed alkyne-containing phenol-based biaryls, where a series of indolone-, azaindoline-, dihydrobenzofuran-, dihydrobenzopyran-, and hydroquinoline-containing spirocyclohexadienone derivatives were synthesized in a single synthetic sequence (Scheme a) …”
Section: Introductionmentioning
confidence: 99%
“…The domino reactions of the synthesis of them were summarized mainly as follows: (i) the Pd or Ni-catalyzed cyclocarbopalladation/coupling fractions, in which the process was initiated by Heck cyclization of a starter (halide) and a relay (alkene), followed by intermolecular coupling reactions with a terminator (organometallic reagents, alkenes, alkynes, etc. ), including Suzuki, Stille, Heck, Sonogashira, C-H activation, carbonylation and amination and so forth [15][16][17]22,24,25,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]; (ii) the C-H oxidative radical coupling reactions, in which these transformations were based on tandem radical addition/cyclization in the presence of oxidants with/without metal catalysts [18][19][20][21]23,26,[45][46][47][48][49][50][51][52][53][54][55]; and (iii) the other reactions [24,[56][57][58][5...…”
Section: Introductionmentioning
confidence: 99%